Spectroscopy of nanosized composites silicon-organic polymer/nanoporous silicas - Ostapenko, N.; Kozlova, N.; Suto, S.; Watanabe, A. (Физика низких температур, 2006)
Fluorescence and excitation spectra (T = 5–290 K) of nanosized silicon–organic polymers
poly(di-n-hexylsilane) and poly(methyl(phenyl)silane) incorporated into porous silica materials
MCM-41 and SBA-15 have been studied with varying pore diameter from 2.8 to 10 nm. The controlled
variation of the pore diameter in the wide range (2.8–10 nm) permitted us, for the first
time, to investigate the optical properties of the polymers on their transition from isolated
macromolecules to a film. It is found that this transition depends on polymer type and occurs via
the formation of new spatially independent structures of the polymers not observed in the spectra
of the film, namely, via the formation of disordered and (or) ordered conformations of polymer
chains and clusters.